Simulation of lead free heterojunction n-FASnI3/p-FrGeCl3 based Perovskite solar cell with ZnMgO as Electron transport layer and GO as Hole transport layer using SCAPS-1D - Dhivya Bharathi C; P. Sriramalakshmi (Results in Engineering)
In this work, a hybrid organic-inorganic perovskite solar cells (PSCs) are studied through SCAPS-1D modeling. The modeling work focuses on heterojunction solar cell featuring dual absorber (n-FASnI3/p-FrGeCl3) layers to enhance the power conversion efficiency (PCE) of charge carrier separation and charge transport. By optimizing the band alignment between the two absorber layers and introducing built-in electric fields, the design aims to improve the overall performance of the solar cell. The present investigation has used an n-p heterojunction (n-FASnI3/p-FrGeCl3) PSC combined with graphene oxide (GO) and ZnMgO as the hole transport layer (HTL) and electron transport layer (ETL) respectively because of its exceptional electrical, mechanical, thermal, and optical characteristics. Hybrid organic-inorganic devices is developed as a result of the incorporation of graphene into the device's structure, which has increased their effectiveness. It is shown that the GO layer promotes hole transportation and improves interaction with the absorber layer. Using SCAPS-1D software, the impact of the n-FASnI3/p-FrGeCl3 heterojunction structure is examined. The FTO/ZnMgO/n-FASnI3/p-FrGeCl3/GO/Au structure improves PCE and decreases recombination losses, according to simulation results with optimized parameters. This innovative approach resulted in a PCE of 32.97%, indicating a significant advancement in photovoltaic technology. In n-FASnI3/p-FrGeCl3 heterojunction structure, optimized conditions result in an open circuit voltage (Voc) of 0.94 V, short circuit current density (Jsc) of 41.03 mA/cm2, and fill factor (FF) of 84.89%. This work confirms that the n-FASnI3/p-FrGeCl3 heterojunction structure is beneficial for creating highly efficient PSCs that minimizes carrier recombination losses.